2014
DOI: 10.1155/2014/629016
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Inflammation in Uveal Tract in Aged Obese Type 2 Diabetic Rats (Spontaneously Diabetic Torii Fatty Rats)

Abstract: We report uveitis observed in an obese type 2 diabetes rat model, Spontaneously Diabetic Torii Leprfa (SDT fatty) rats aged over 50 weeks. The eyes of SDT fatty rats (16 animals: 7 males and 9 females with 50 or 60 weeks of age) were examined histopathologically. Infiltration of inflammatory cells in the uveal tract was observed in 13 of 16 animals. One female showed severe inflammation affecting the entire uveal tract including the iris, ciliary body, and choroid with a variety of inflammatory cells (neutroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Kemmochi and colleagues21 have suggested that diabetes might be one of the contributing factors to the better inflammatory control of uveitis because drugs for diabetes improved carbohydrate metabolism and also decreased ocular inflammation. Furthermore, Scheen and colleagues22 have reported that several antidiabetic drugs used in clinical practice for patients with diabetes exert anti-inflammatory effects partly as a result of reducing high blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Kemmochi and colleagues21 have suggested that diabetes might be one of the contributing factors to the better inflammatory control of uveitis because drugs for diabetes improved carbohydrate metabolism and also decreased ocular inflammation. Furthermore, Scheen and colleagues22 have reported that several antidiabetic drugs used in clinical practice for patients with diabetes exert anti-inflammatory effects partly as a result of reducing high blood glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, with the prevalence of T2D, the dysfunction of multiorgans manifests a similarly trend compared with the chronological senescence (Kuki et al, 2006). Accumulating evidence has manifested that and these changes may also lead to the production of diabetes (Kemmochi et al, 2014). Therefore, there have been corresponding…”
Section: Diabetes and Aging Modelsmentioning
confidence: 99%
“…Giving elderly mice a short‐term high‐fat/high‐sucrose diet can also induce an aging diabetes model, which mouse model has weight gain and glucose intolerance, and its fasting insulin is closely related to the insulin secretion stimulated by glucose in the body (Li et al., 2014). During the aging process, the physiological functions of mammals have undergone major changes, and these changes may also lead to the production of diabetes (Kemmochi et al., 2014). Therefore, there have been corresponding senescence‐induced senescent diabetes models, the induction models include d ‐galactose induction, age induction, transgenic premature senescence mice, and so on.…”
Section: Diabetes and Aging Modelsmentioning
confidence: 99%
“…Therefore, advancing the development of ocular complications is meaningful for studying diabetic retinopathy using experimental animal model. In addition, according to obesity and following insulin resistance, inflammation is found in eyes in SDT fatty rat at older age (Kemmochi et al 2014). Also, further studies are needed to unveil the difference of response to various drugs, such as SGLT2 inhibitor, between SDT and SDT fatty rat.…”
Section: Discussionmentioning
confidence: 99%